Cybergogy: Konsep dan Implementasi dalam Pembelajaran Phonology Program Studi Tadris Bahasa Inggris - Aminah, Sitti; Irmayani; Sabaruddin; Restu Ramadhan, Andi; Jusriani; Mujahid, Ayinun (Prosiding Seminar Nasional Fakultas Tarbiyah dan Ilmu Keguruan IAIM Sinjai, 2023)
As we know, information and communication technology are developing rapidly in this era. This ever-evolving and improving technology has led to increased learning and innovation opportunities associated with newer information and communication technology systems. Along with the development of this technology, improving the quality of human resources is also needed, so that the world of education needs to take steps to innovate learning methods. Therefore, the English Tadris Study Program proposes a learning method through the concept of cybergogy as an involved online learning system. Cybergogy is a learning innovation based on information and communication technology with three interrelated factors, namely: cognitive, emotional, and social. The purpose of this study is to provide an overview of the concept and implementation of cyberphony in learning phonology. The method used in this research is a literature study. Data collection techniques include searching for data in books, journals, and the web (internet) with data analysis using the theory of Miles and Huberman. The results and discussion of this study on phonology can be applied to the learning process with the cybergogy method. Learning phonology through the concept of cybergogy can be easily understood because phonology studies sound, and this learning is very compatible with the concept of cybergogy, which is learning with native speakers through online media.